Nicotine- N ′-Oxidation by Flavin Monooxygenase Enzymes - Perez-Paramo, Yadira X.; Chen, Gang; Ashmore, Joseph H.; Watson, Christy J. W.; Nasrin, Shamema; Adams-Haduch, Jennifer; Wang, Renwei; Gao, Yu-Tang; Koh, Woon-Puay; Yuan, Jian-Min; Lazarus, Philip (Cancer epidemiology, biomarkers & prevention, 2019)
The major mode of metabolism of nicotine is by hydroxylation via cytochrome P450 (CYP) 2A6, but it can also undergo glucuronidation by UDP-glucuronosyltransferases and oxidation by flavin monooxygenases (FMO). The goal of this study was to examine the potential importance of FMOs in nicotine metabolism and assess the potential impact of missense polymorphisms in active FMOs on nicotine- '-oxide (NOX) formation. Urine samples from 106 current Chinese smokers were analyzed for nicotine metabolites by mass spectrometry. Wild-type s 1-5 and their most prevalent nonsynonymous variants were cloned and overexpressed in HEK293 cells, and were tested in oxidation reactions against nicotine. A strong inverse correlation was observed between the ratio of urinary 3'-hydroxycotinine/cotinine, a measure of CYP2A6 activity, and the urinary levels of NOX alone ( = -0.383; < 0.001) or NOX measured as a ratio of total nicotine metabolites ( = -0.414; < 0.001) in smokers. In addition to FMO1 and FMO3, the functional FMO2 isoform was active against nicotine, whereas FMO4 and FMO5 exhibited low activity against nicotine ( > 5.0 mmol/L). Significant ( < 0.05) decreases in '-oxidation activity ( / ) were observed for the FMO1 , FMO3 , FMO3 , FMO3 , and FMO3 variants when compared with their respective wild-type isoforms; the truncated FMO2 isoform exhibited no enzyme activity. These data indicate that increases in nicotine- '-oxidation occur in subjects with deficient CYP2A6 activity, and that several FMO enzymes are active in nicotine- '-oxidation. Several common missense FMO variants are associated with altered enzyme activity against nicotine and may play an important role in nicotine metabolism in low-CYP2A6 activity subjects.